Challenges of Medical Care Delivery in Professional Sports: Lessons From Professional Baseball. Issue 24 (15th December 2018) - Duralde, Xavier; Jones, Troy; Griffith, Timothy
Abstract : Team medical management for professional sports teams is a demanding and high-risk activity. Every different sport has unique features and the stresses athletes place on themselves, be it from collisions or repetitive stress, result in specific challenges for the medical team and team organization in general. Injuries in professional sports are costly both to the player and organization. The challenges of managing a professional baseball team exemplify these concerns and correlate well with other professional sports. Multiple strategies exist for improvement of medical care in baseball based on observed deficiencies in player evaluation, injury prevention, and injury treatment, which will require prospective evaluation to determine their success. These include draft strategies, individualized motion and strength analyses, customized in-season and off-season training programs for individuals, and standardized treatment protocols for injuries all based on best practices. Best practices are currently poorly defined in all of these areas.